Advanced MALDI mass spectrometry imaging in pharmaceutical research and drug development. (February 2019) - Schulz, Sandra; Becker, Michael; Groseclose, M. Reid; Schadt, Simone; Hopf, Carsten
Graphical abstract: Highlights: Ideal mass spectrometer for MALDI MSI would satisfy the '4S-criteria for performance' (speed, specificity, spatial resolution and sensitivity). Quantification MALDI MSI is achieved by spotting calibration curves onto control tissue sections or by using mimetic tissue models. Stable isotope standards are most commonly used for signal normalization in quantitative MSI. Further Validation and multi-site studies are required for best practices in wet lab, 'big data' processing and reporting. Besides drug disposition studies, investigation of target engagement, PK/PD and drug-induced toxicity is drawing more attention. Abstract : Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) has emerged as a key technology for label-free bioanalysis of the spatial distribution of biomolecules, pharmaceuticals and other xenobiotics in tissue sections. Recent advances in instrumentation, sample preparation, multimodal workflows, quantification, analytical standardization and 'big data' processing have led to widespread utilization of MALDI MSI in pharmaceutical research. These developments have led to applications of the technology in drug discovery beyond drug disposition analysis, most notably in pharmacodynamic biomarker research and in toxicology.